Single-Operator Ultrasound-Guided Central Venous Catheter Insertion Verifies Proper Tip Placement*. Issue 10 (October 2017) - Galante, Ori; Slutsky, Tzachi; Fuchs, Lior; Smoliakov, Alexander; Mizrakli, Yuval; Novack, Victor; Brotfein, Evgeni; Klein, Moti; Frenkel, Amit; Koifman, Leonid; Almog, Yaniv
Abstract : Objectives: To evaluate whether a single-operator ultrasound-guided, right-sided, central venous catheter insertion verifies proper placement and shortens time to catheter utilization. Design: Prospective observational study with historical controls. Setting: Adult ICUs. Patients: Sixty-four consecutive patients undergoing ultrasound-assisted right-sided central venous catheterization compared with 92 serial historic controls who had unassisted central catheter insertion at the same sites. Interventions: Subcostal transthoracic echocardiography during catheter insertion. Measurements and Main Results: The primary outcome was the correct placement of the catheter tip determined by postprocedural chest radiography. The subclavian site was used in 41 patients (64%) (inserted without ultrasound guidance) in the ultrasound-assisted group and 62 (67%) in the control group, whereas the jugular vein was used in the remaining patients. The tip was accurately positioned in 59 of 68 patients (86.7%) in the ultrasound-assisted group compared with 51 of 94 (54.8%) in the control group ( p < 0.001). The median time from end of the procedure to catheter utilization after chest radiography approval was 2.4 hours. Conclusions: A single-operator ultrasound-guided central venous catheter insertion is effective in verifying proper tip placement and shortens time to catheter utilization.